2005
DOI: 10.1080/08035250510028894
|View full text |Cite
|
Sign up to set email alerts
|

Maternal perception of excess weight in children: A survey conducted by paediatricians in the province of Milan

Abstract: A better understanding of how mothers perceive the problem of excess weight in their children is relevant to the success of preventive interventions in childhood obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
68
4
15

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 20 publications
(13 reference statements)
9
68
4
15
Order By: Relevance
“…[4][5][6][7][8][9] Misclassification of overweight children was specifically associated with child male gender, dissatisfaction, dieting and higher maternal BMI. The findings that essentially 40% of mothers failed to correctly classify their overweight child as 'overweight' can be explained in at least three possible ways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7][8][9] Misclassification of overweight children was specifically associated with child male gender, dissatisfaction, dieting and higher maternal BMI. The findings that essentially 40% of mothers failed to correctly classify their overweight child as 'overweight' can be explained in at least three possible ways.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have found that parents underestimate the weight status of their overweight or obese child [4][5][6][7][8][9][10][11][12] in both population and clinical research settings. Parents weight status estimation is worse for younger rather than older children 9 and possibly for mothers with poorer educational attainment, 4 but is more accurate for daughters rather than for sons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Active participation in such strategies, however, depends partly on the ability of parents to recognize when their child is overweight. Several studies have explored parents' perception of their child's weight status (5,(23)(24)(25) . Questionnaires are often used to record their responses by means of selecting a word response to a question or by providing images of different body shapes as a comparator (2,3,5,26) .…”
Section: Discussionmentioning
confidence: 99%
“…The parents' responses are then compared with their child's actual weight status which is categorized as thin, normal, overweight or obese, usually by BMI. In the past, large discrepancies have been noted between perception and measured overweight status, with far fewer parents classifying their child as overweight or obese compared with what was actually measured (23,25,27,28) . The aim of the present analysis was to investigate which anthropometric WHtR, waist-to-height ratio.…”
Section: Discussionmentioning
confidence: 99%